Lumbar Discal Cyst: Is it a Rare Consequence in Lumbar Disc Disease Spectrum? Short Case Series with Review of Literature and Hypothesis Regarding Etiopathogenesis - Usha Kota Narayana Pai; Devaprasad Sathyanarayanan; Harsha Manjarambath Haridas (Indian Journal of Neurosurgery)
Background Lumbar discal cysts are rare intraspinal extradural lesions presenting as lumbar radiculopathy. The rarity of the lesion is sufficient to evoke interest in its diagnosis. The hitherto unsolved etiopathogenesis prompted us to look into these areas in this study. Objectives 1) To review the literature and summarize the clinicoradiological and histopathological features of the discal cyst. 2) To investigate possible mechanisms in the etiopathogenesis of discal cysts. Materials and Methods Three patients presented with features suggestive of lumbar disc prolapse and were diagnosed with discal cyst over 1.5 years and were included in this study. All patients underwent lumbar spine magnetic resonance imaging (MRI) and were subsequently treated by cyst excision. The final diagnosis of the discal cyst was based on histopathological features. Results Out of three patients, two had a discal cyst with disc prolapse, and one had a discal cyst alone. Discal cyst patient underwent excision of cyst alone. Discal cyst patients with disc prolapse underwent discectomy in addition to excision of the discal cyst. One patient had an L2–L3 level discal cyst with disc prolapse, which is uncommon. Conclusions Lumbar discal cysts, although rare, form an important differential diagnosis in patients with lumbar radiculopathy. They have a distinctive MRI appearance, and because discal cyst and disc prolapse shared similar etiopathological features, we hypothesize that discal cyst is a part of the degenerative disc disease spectrum. We also conclude that discal cyst excision should be coupled with discectomy when LDC is associated with disc prolapse.